Participation trends of children in regional cross-country final during three seasons - Vílchez, M. P.; Molina, J. M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2014)
Sports at school age are a useful tool of sports promotion, which its participation is growing (CSD, 2009; Valovich et al., 2011). Concretely, cross-country running is a sport that has simple characteristics to be able to improve that promotion. For this reason, in the following study, the participation of scholars on cross-country events from seasons 2010-11, 2011-12 and 2012-13 is analyzed to know the characteristics of scholar participation and to be able to guide promotion sports tasks of corresponding entities. A sample of 4205 participations of scholars on cross-country events was used. From the total sample, 51.4% were boys and 48-6% were girls. Data analysis was made using statistics programme SPSS, version 21. It was concluded that it has been developed a great promotion tasks between girls, however, there exists a need to improve sports promotion programmes in older scholars and also among private schools.